The efficacy and safety of radiofrequency ablation in papillary thyroid carcinoma: A systematic review and meta-analysis - Wei Shuen Clarissa Cheong; Xin Yi Joy Au; Ming Yann Lim; Ernest Weizhong Fu; Hao Li; Uei Pua; Yong Quan Alvin Soon; Yijin Jereme Gan (Annals, Academy of Medicine, Singapore)
Introduction: Radiofrequency ablation (RFA) avoids the complications of general anaesthesia, reduces length of hospitalisation and reduces morbidity from surgery. As such, it is a strong alternative treatment for patients with comorbidities who are not surgical candidates. However, to our knowledge, there have only been 1 systematic review and 3 combined systematic review and meta-analyses on this topic to date. This systematic review and meta-analysis seeks to evaluate the efficacy and safety of RFA in the treatment of papillary thyroid carcinoma (PTC) with longer follow-up durations. Method: PubMed, Embase and Cochrane databases were searched for relevant studies published from 1990 to 2021; 13 studies with a total of 1366 patients were included. The Preferred Reporting Items for Systematic reviews and Meta-Analyses guidelines and Sandelowski et al.’s approach1 to “negotiated consensual validation” were used to achieve consensus on the final list of articles to be included. All authors then assessed each study using a rating scheme modified from the Oxford Centre for Evidence-Based Medicine. Results: Pooled volume reduction rates (VRRs) from 1 to 48 months after RFA, complete disappearance rates (CDR) and complications were assessed. Pooled mean VRRs were 96.59 (95% confidence interval [CI] 91.05–102.13, I2=0%) at 12 months2-6 and 99.31 (95% CI 93.74–104.88, I2=not applicable) at 48 months.2,5 Five studies showed an eventual CDR of 100%.2,4,7-9 No life-threatening complications were recorded. The most common complications included pain, transient voice hoarseness, fever and less commonly, first-degree burn. Conclusion: RFA may be an effective and safe alternative to treating PTC. Larger clinical trials with longer follow-up are needed to further evaluate the effectiveness of RFA in treating PTC.